Association between Plasma Short-Chain Fatty Acids and Hypertensive Disorders of Pregnancy: A Nested Case-Control Study - Dandan Wang; Lei Wu; Pei Feng; Yexiu Sun; Di Wu; He Xu; Hao Peng; Hongmei Li (Maternal-Fetal Medicine, 2026)
Abstract Objective: To investigate the associations between plasma short-chain fatty acids (SCFAs) and hypertensive disorders of pregnancy (HDP). Methods: A nested case-control study was conducted comprising 387 pairs of HDP cases and non-HDP controls. The HDP group included 291 cases of gestational hypertension (GH) and 96 of preeclampsia (PE) or chronic hypertension (CH) with superimposed PE (PE/CH-PE). Seven plasma SCFA levels were assayed at gestational weeks 16–20, before HDP onset. The individual effects of the seven SCFAs on HDP risk were analyzed using logistic regression, with false discovery rate (FDR) correction applied to calculate adjusted P -values in multivariate analysis. The joint effects of the seven SCFAs were evaluated using weighted quantile sum (WQS) regression. Results: HDP cases exhibited significantly lower median (interquartile range) valerate levels than controls (9 (5–14) vs . 10 (6–18) ng/mL, P = 0.001). Among the seven analyzed SCFAs, isobutyrate and isovalerate demonstrated the highest correlation coefficient at 0.85 ( P < 0.001). Each interquartile range increase in valerate content was associated with a 30.1% reduction in HDP risk, yielding an adjusted odds ratio (a OR ) of 0.699 (95% confidence interval ( CI ): 0.516–0.946, FDR-corrected P = 0.047). Isobutyrate and hexanoate were also inversely associated with HDP after multivariate adjustment and FDR correction (both P = 0.047), with a OR s of 0.899 (95% CI : 0.826–0.980) and 0.686 (95% CI : 0.508–0.927), respectively. WQS regression revealed that joint SCFA exposure was associated with a decreased risk of HDP (a OR : 0.230, 95% CI : 0.105–0.506) and GH (a OR : 0.740, 95% CI : 0.571–0.933). Conclusion: Plasma levels of valerate, isobutyrate, and hexanoate are inversely associated with HDP risk. Furthermore, the combined effect of these SCFAs is linked to a lower incidence of both HDP and GH. These findings suggest that circulating SCFAs may serve as potential early biomarkers for HDP.